Interplay Between Gut Microbiota and Amino Acid Metabolism in Heart Failure - Tuerhongjiang, Gulinigaer; Guo, Manyun; Qiao, Xiangrui; Lou, Bowen; Wang, Chen; Wu, Haoyu; Wu, Yue; Yuan, Zuyi; She, Jianqing (Frontiers in Cardiovascular Medicine, 2021)
Heart failure (HF) is a complex clinical syndrome of which the incidence is on the rise worldwide. Cardiometabolic disorders are associated with the deterioration of cardiac function and progression of HF. Recently, there has been renewed interest in gut microbiota (GM) and its metabolites in the cardiovascular disease. HF-caused hypoperfusion could increase intestinal permeability, and a “leaky” bowel leads to bacterial translocation and make its metabolites more easily enter the circulation. Considerable evidence shows that the composition of microbiota and amino acids (AAs) has been altered in HF patients, and AAs could serve as a diagnostic and prognostic biomarker in HF. The findings indicate that the gut–amino acid–HF axis may play a key role in the progression of HF. In this paper, we focus on the interrelationship between the AA metabolism and GM alterations during the development of heart failure. We also discuss the potential prognostic and therapeutic value of the gut–amino acid–HF axis in the cortex of HF.